STEM teacher education in Germany: Organization, expectations and challenges from the perspectives of the subjects mathematics and physics - Lindmeier, Anke; Neumann, Knut (Taylor and Francis, 2021)
This chapter examines teacher education programmes for secondary-level STEM in Germany. As there is no dedicated technology or engineering education in Germany at the secondary level, we will narrow our focus to mathematics and physics teacher education. The chapter will discuss the principal structure and the specific components of teacher education programmes for secondary teachers in Germany. Analysis of national teacher education standards and programme-specific syllabi provides insights into the expectations of teacher education programme graduates, who study two subjects in Germany. The analysis reveals that secondary teacher education in Germany aims to provide graduates with a profound knowledge of the subject matter as well as knowledge about how to teach the subject matter. The chapter concludes by highlighting current issues of teacher education from the perspective of both subjects: mathematics and physics.
CRIS-Team Scopus Importer:2024-10-02